1997
DOI: 10.3109/08037059709062092
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Blood Pressure and Relation to Vasoactive Hormones and Renal Function in Hypertension and Chronic Renal Failure

Abstract: The purpose of this study was to assess the blood pressure profile and to measure vasoactive hormones in patients with essential hypertension (n=61), secondary hypertension (n=32) and chronic renal failure (n=32) matched with healthy control subjects (n=35), and to study the relationship between circadian changes in blood pressure and baseline levels of vasoactive hormones and renal function. Non-invasive, automatic blood pressure measurement was performed for 24 or 48 h. Venous plasma concentrations of renin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…25 The synthesis of these peptides is upregulated in pressure and volume overload, 20,[25][26][27] as in patients with renal failure. 28,29 In this study, the ventricular levels of ANP mRNA were increased in NTX groups, whereas elevated levels of NT-proANP in plasma indicate that the release of ANP was increased. 25 Ventricular concentrations of BNP mRNA and BNP peptide were also increased in NTX rats.…”
Section: Discussionmentioning
confidence: 82%
“…25 The synthesis of these peptides is upregulated in pressure and volume overload, 20,[25][26][27] as in patients with renal failure. 28,29 In this study, the ventricular levels of ANP mRNA were increased in NTX groups, whereas elevated levels of NT-proANP in plasma indicate that the release of ANP was increased. 25 Ventricular concentrations of BNP mRNA and BNP peptide were also increased in NTX rats.…”
Section: Discussionmentioning
confidence: 82%
“…In a study of normotensive (n = 27) and hypertensive (n = 41) patients with chronic renal insufficiency, and matched control groups, the renal patients showed significantly blunted nocturnal pressure reduction compared with their respective control groups (P < 0.01 and P < 0.001, respectively), wider distribution of BP values; and a greater nocturnal variability [38]. Similarly, Jensen and Pedersen [39] studied patients with essential hypertension (n = 61), secondary hypertension (n = 32), and chronic renal failure (n = 32) matched with healthy control subjects (n = 35), and demonstrated that nighttime BP was higher among the chronic renal failure patients than in the control group, and the nightly fall in BP was reduced. Similar data about the lack of nocturnal BP decline in patients with chronic renal insufficiency have been reported in other studies [40,41].…”
Section: Ambulatory Blood Pressure and Diurnal Variation And Chronic mentioning
confidence: 84%
“…In addition, we found [14] that the GFR was an independent factor affecting the nocturnal MAP fall in the sodium-sensitive type of essential hypertension. A positive correlation between GFR and nocturnal BP dip was also reported in both essential hypertension and chronic renal failure [23]. These findings suggest that the circadian rhythm of the BP is determined at least in part by the kidneys and their sodium handling.…”
Section: Discussionmentioning
confidence: 54%